HSP70/HSF1 axis, regulated via a PI3K/AKT pathway, is a druggable target in chronic lymphocytic leukemia. Issue 11 (15th May 2019) - Frezzato, Federica; Raggi, Flavia; Martini, Veronica; Severin, Filippo; Trimarco, Valentina; Visentin, Andrea; Scomazzon, Edoardo; Accordi, Benedetta; Bresolin, Silvia; Piazza, Francesco; Facco, Monica; Basso, Giuseppe; et al.
Abstract : Considering the role played by the heat shock protein of 70 kDa (HSP70) in cancer, we characterized this protein and its major regulator, the heat shock factor 1 (HSF1), in chronic lymphocytic leukemia (CLL). We found both HSP70 and HSF1 overexpressed in CLL patients, correlated to poor prognosis and abnormally localized in the nucleus of leukemic B cells. The two proteins were strictly correlated each other and their levels decreased consensually in those patients responding to in vivo therapeutic regimens. HSP70 and HSF1 inhibition was proved to be effective in inducing a dose‐dependent in vitro apoptosis of CLL B cells. Considering that HSF1 is finely regulated by kinases belonging to pathways triggered by rat sarcoma (RAS), we benefited from a previous proteomic study performed in CLL patients aiming to assess the activation/expression of key signaling proteins. We found that patients showing high levels of HSP70 also expressed high Akt‐Ser473, thus activating HSF1. Inhibition of PI3K, which activates AKT, reduced the expression of HSF1 and HSP70. By contrast, HSP70‐low patients displayed high activation of MEK1/2 and ERK1/2, known to negatively regulate HSF1. These data demonstrate that the HSP70 expression is regulated by the modulation of HSF1 activity through the activation of RAS‐regulated pathways and suggest the HSP70/HSF1 interplay as an interesting target for antileukemic therapies. Finally, inhibition of PI3K, that activates AKT, reduced the expression of HSF1 and HSP70. Abstract : What's new? The heat shock protein HSP70 is overexpressed in B cells from chronic lymphocytic leukemia (CLL) patients but how it contributes to leukemogenesis is unknown. Here, the authors identify its interaction with the heat shock factor HSF1 as a possible mechanism. HSF1 is activated by the phosphoinositide‐3‐kinase–protein kinase B (PI3K/AKT) signal transduction pathway, and inhibition of PI3K reduced the expression of both HSP70 and HSF1. Similarly, HSP70 or HSF1 inhibition induced cell death, supporting the notion that both represent possible targets in CLL treatment.